THz Transmission through Submillimeter Apertures - LaFave, T.; Lee, A.; Kao, T.-Y.; Markelz, A. (IRMMW-THz, 2020)
Terahertz near-field microspectroscopy is emerging as an essential tool for characterization of novel materials and biomolecules. It is important to ensure the near field geometry used does not introduce spectral artifacts. For example, many scanning techniques can be strongly influenced by the interaction between the scattering tip and the sample. Here we examine the spectroscopic effects of a 200 μm diameter aperture for THz near-field measurements. We use HFSS to model free-space transmission through samples with resonant absorbance as a function of sample thickness, lateral sample width, and aperture diameter. We examine the transmitted power and spectral fidelity for coupling of transmitted THz light onto a detector. These studies inform corrective post-measurement analysis algorithms and design of near-field detection systems.